Application of Bankruptcy Principles and Principles in the Decision of a Special Judge (Ad Hoc) Commercial Court According to Law Number 37 Of 2004 - Lie, Gunardi; Shasmita, Sylvia (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Commercial Court, Cassation, and Judicial Review judges set legal principles and uphold justice. Their bankruptcy decisions should be fair and certain, giving all parties legal advantages. Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations is one bankruptcy judge's instrument. Thus, understanding Indonesian commercial court verdicts' legal grounds and how judges use certainty, fairness, and legal expediency is crucial. The subject is examined using a juridical-descriptive-analytical methodology based on Makassar, Medan, Surabaya, Semarang, and Jakarta commercial court cases. Cluster and stratified sampling, descriptive quantitative data tabulation, qualitative analysis, and interviews have shown three judge-used legal reasoning processes. Inductive patterns oriented to legal expediency by Supreme Court Judges at the Judicial Review level; deductive syllogism patterns oriented to legal certainty by Judex Facti judges in the Commercial Court (level I); and deductive patterns oriented to legal justice by Judex Yuris at the Cassation level. Indonesian commercial court judges apply certainty, fairness, and expediency: First, the legal principles and principles applied in the decision of the first instance judge of the Commercial Court (legal certainty) are debt requirements; bankruptcy decisions cannot be imposed on solvent debtors; bankruptcy decisions must be approved by the majority of creditors; silence; recognition of the separatist rights of creditors holding security rights; the bankruptcy decision process is short and open. Second, Supreme Court justices at the Cassation level use the following legal concepts (legal justice): balance, fairness, potential debtor debt restructuring, parity creditorium, pari passu prorate, and structural creditors. Third, the Supreme Court's Judicial Review judges apply the legal expediency principles of business continuity, integration, encouraging investment and business, providing benefits and protection, bankrupt company management must be personally liable, harming bankruptcy property as a criminal offense, debt collection, debt pooling, debt forgiveness, universal, and territorial